Determinants of Falls and Fear of Falling in Ambulatory Persons With Late Effects of Polio. Issue 5 (18th August 2016) - Brogårdh, Christina; Flansbjer, Ulla‐Britt; Lexell, Jan
Abstract: Background: Falls and fear of falling (FOF) are common in persons with late effects of polio, but there is limited knowledge of associated factors. Objective: To determine how knee muscle strength, dynamic balance, and gait performance (adjusted for gender, age, and body mass index) are associated with falls and FOF in persons with late effects of polio. Design: A cross‐sectional study. Setting: A university hospital outpatient clinic. Participants: Eighty‐one ambulatory persons with verified late effects of polio (43 men; mean age 67 years). Main Outcome Measurements: Number of falls the past year, Falls Efficacy Scale–International to assess FOF, a Biodex dynamometer to measure knee muscle strength, the Timed Up & Go test to assess dynamic balance, and the 6‐Minute Walk test to assess gait performance. Univariate and multivariate logistic regression analyses were used for falls (categorical data) and linear regression analyses for FOF (continuous data) as dependent variables. Results: Fifty‐nine percent reported at least 1 fall during the past year, and 79% experienced FOF. Reduced knee muscle strength in the more affected limb and gait performance were determinants of falls. An increase of 10 Nm in knee flexor and knee extensor strength reduced the odds ratio between 0.70 and 0.83 ( P = .01), and an increase of 100 m in 6‐Minute Walk test reduced the odds ratio to 0.41 ( P = .001). All factors were determinants of FOF; reduced knee muscle strength in the more and less affected limbs explained 17%‐25% of the variance in FOF, dynamic balance 30%, and gait performance 41%. Gender, age, and body mass index only marginally influenced the results. Conclusions: Reduced gait performance, knee muscle strength, and dynamic balance are to a varying degree determinants of falls and FOF in ambulatory persons with late effects of polio. Future studies need to evaluate whether rehabilitation programs targeting these factors can reduce falls and FOF in this population. Level of Evidence: IV